A efetividade do direito à informação ambiental - BARROS, Lucivaldo Vasconcelos (Universidade de Brasília, 2017)
This research presents a reflection on the right to information as an instrument for strengthening participatory processes in the defense of environmental heritage and in harmony with the principles of sustainable development. Its main focus is on the transfer of information during the public hearing stage in environmental licensing processes. The principles, concepts and practices of the public participation process are analyzed, especially those regarding the dissemination of environmental information. The interferences in its access, as well as its origins and typologies are indicated, from the most common communication barriers to structural political and economic influences. Consequences due to difficulties in the access to information are shown as well as their reflexes on the role of law and ethics in the process. Historic and conceptual issues of the Rule of Law are presented in order to approach the right to information in a broader way, particularly as an instrument of democracy. The importance of democracy in the awareness of environmental protection is stressed. The importance of public information and a legal view of the right to environmental information in a national and international level is presented. Environmental management aspects in Brazil such as the environmental impact assessment process are taken into account as well as a study on public hearings as instruments for access to environmental information. This approach is based on interviews with different stakeholders and on research developed upon documents of public hearings in three processes of federal environmental licensing of hydroelectric projects. The analysis based on documents as well as on interviews helped consolidate the theories and hypothesis formulated in this research. A need for behavioral changes in the current practices is indicated, especially regarding the transparency of those demanded by the government in order to incorporate ethical principles capable of effectively transforming those practices.